(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 65-year-old male hailing from Lolua, Tangail north bordering district of Dhaka, Bangladesh, reported to the Department of Hematology, Armed Forces Institute of Pathology with the complaints of marked weight loss, generalized weakness, low-grade fever and anorexia. He was referred from Kurmitola General Hospital, Dhaka, Bangladesh for bone marrow aspiration and examination. Before aspirating the bone marrow, a detailed history was taken which revealed that he had been suffering from the above mentioned symptoms for the last 10 months. During this time, he reported to the local physicians who investigated with routine laboratory tests such as complete blood count, peripheral blood film